Liquidez y rentabilidad en la empresa Mar Moz Panes y Pasteles S.R.L. Iquitos, período 2018 – 2022 - Ramirez Crispin, Luis Alexander (2023)
The main purpose of the study was to carry out the analysis of liquidity and profitability in the Company Mar Moz Panes y pastels S.R.L. of Iquitos in the period 2018–2022. Contemplated by a basic research, descriptive level and non-experimental design, it has taken the financial statements of the specified period, using the technique of documentary analysis, recording the information through a form according to the data required by the formulas of ratios. Thus, the study concluded that the company has maintained high levels of liquidity in the last 5 years, evidencing a strong capacity to cover its short-term commitments. However, fluctuations between 2019 and 2021 suggest possible changes in the management of current assets and liabilities. Although liquidity is a positive sign, excessively high figures could signal inefficiencies or risk aversion in investments. The company has maintained a defensive ratio greater than 1 and positive working capital throughout these years, demonstrating financial solidity. However, there were notable fluctuations in working capital and cash conversion cycle, with worrying increases in 2019 and 2022. In terms of profitability, from 2018 to 2021, the company showed growth in both return on assets and in profitability on equity.